P2X7 Receptors in Neurological and Cardiovascular Disorders. (25th May 2009) - Skaper, Stephen D.; Debetto, Patrizia; Giusti, Pietro
Abstract : P2X receptors are ATP-gated cation channels that mediate fast excitatory transmission in diverse regions of the brain and spinal cord. Several P2X receptor subtypes, including P2X 7, have the unusual property of changing their ion selectivity during prolonged exposure to ATP, which results in a channel pore permeable to molecules as large as 900 daltons. The P2X 7 receptor was originally described in cells of hematopoietic origin, and mediates the influx ofCa 2 + andNa + andCa 2 + andNa + ions as well as the release of proinflammatory cytokines. P2X 7 receptors may affect neuronal cell death through their ability to regulate the processing and release of interleukin-1β, a key mediator in neurodegeneration, chronic inflammation, and chronic pain. Activation of P2X 7, a key mediator in neurodegeneration, chronic inflammation, and chronic pain. Activation of P2X 7 receptors provides an inflammatory stimulus, and P2X 7 receptor-deficient mice have substantially attenuated inflammatory responses, including models of neuropathic and chronic inflammatory pain. Moreover, P2X 7 receptor activity, by regulating the release of proinflammatory cytokines, may be involved in the pathophysiology of depression. Apoptotic cell death occurs in a number of vascular diseases, including atherosclerosis, restenosis, and hypertension, and may be linked to the release of ATP from endothelial cells, P2X 7 receptor activation, proinflammatory cytokine production, and endothelial cell apoptosis. In this context, the P2X 7 receptor may be viewed as a gateway of communication between the nervous, immune, and cardiovascular systems.